Undermining the Role of Women in the Economy: The Interplay Between Paid Work and Unpaid Care Work in India. (21st December 2021) - Vyas, Neha
Abstract: Women are overrepresented in informal employment in the Indian labour market. They also devote more time to unpaid care work than men do. The poor working conditions of women are attributable to this double burden of work. Due to the lack of regulatory measures to protect the interest of informal women workers along with rigid gender norms, women's participation in paid work is drastically reduced. As far as unpaid care work is concerned, feminist economists have been striving to make such work visible for a long time now. There have been some developments in labour statistics, with time use surveys quantifying women's paid and unpaid contributions to the economy. This article delves into the examination of unpaid care work in India with the help of the Indian government's recent Time Use Survey. It attempts to study the connection between paid work and unpaid care work and its implications for the working conditions of women in India. Finally, it evaluates the 'right to work' as a possible solution by using the example of employment guarantee schemes in India.